PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SDN 006 TELUK SEJUAH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Fitri, Syamsul; Marhadi, Hendri; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to improve learning outcomes IPA class fourth students of SDN 006 Teluk Sejauh Kecamatan Kelayang Kabupaten Indragiri Hulu with application of learning models Contextual Teaching and Learning (CTL). The subjects were students of class IV totaling 17 students, consisting of 9 men and 8 women. This type of research is a classroom action research. Based on the results of this study concluded that the application of learning models CTL can improve learning outcomes IPA fourth grade students of SDN 006 Teluk Sejauh Kecamatan Kelayang Kabupaten Indragiri Hulu. The average value of daily test applied science students before learning model CTL is 60.58. In the first cycle UH 1 daily value increased to 70.59 students who have increased as much as 16.52%, with the number of students who completed 12 students. In the second cycle increased the average value of as much as 48.08% to 89.71. All students completed the implementation of the UH 2. The increase is supported by the activities of teachers and students. In the first cycle of meetings to-1 activity for teachers to get success 71.42% with good criteria. At the 2nd meeting increased to 82.14% with good criterion. Observation activities of teachers in the second cycle to-one meetings to acquire 89.28% success with good criteria. At the 2nd meeting increased to 92.85% by qualifying was very good. Student activity student activity during the application of learning models CTL in the first cycle-one meetings to gain success 71.42% with good criteria. At the 2nd meeting increased to 85.71% with good criteria. In the second cycle to meeting all first gained 89.28% success with good criteria. At the 2nd meeting meningkaat be 92.85% with a qualifying was very good. Thus, it can be concluded that the application of learning models CTL can improve learning outcomes IPA class fourth students of SDN 006 Teluk Sejauh Kecamatan Kelayang Kabupaten Indragiri Hulu.Â Keywords : Learning Model CTL, Learning Outcomes IPA